Inclusive Education System In Armenia And Perspectives For Its Development - Arakelyan, Hasmik
This article examines to what extent Armenia has advanced in inclusive education and the remaining institutional, social, cultural, and attitudinal barriers hindering the smooth implementation of universal inclusive education. It examines why it is important to include children with disabilities in mainstream classes and favorable attitudes toward inclusive education among teachers, administrators, and children. Inclusive education is the process of integrating individuals with disabilities into regular classrooms, and it helps reflect the commitment to equal educational opportunities as outlined in the UN Convention on the Rights of Persons with Disabilities (United Nations, 2006). Inclusive education assumes that diverse and unique students are learning side by side within the same school and classroom context. It treasures each student's unique contribution to the learning process (Open Society Foundation, 2019). However, the definition somehow conceals the complexity of inclusive education, which requires appropriate strategies, inputs, and benchmarking. The Inclusive Education system was officially embraced in 2003 and has more than 20 years of history. In the meantime, many barriers hinder its implementation, such as a lack of professional development for teachers, reasonable accommodations, assistive technologies, difficulty creating relationships between classmates, inadequate parent participation, and necessary operational procedures aligned to its practice.
Keywords: Education